6. MOTHERS’ KNOWLEDGE, ATTITUDES ON CARE OF THEIR CHILDREN WITH COVID-19 BEING TREATED AT HOME IN PHU QUOC CITY, KIEN GIANG PROVINCE, IN 2022 (Vietnam Journal of Community Medicine, 2023)
Objective: During the COVID-19 pandemic, the disease has extremely affected children’s physical and mental health. The role of mothers caring for their children with COVID-19 is very important, especially for those who are isolated and treated at home. Thus, research on the status of the mothers’ knowledge and attitudes is strictly necessary.Research subjects and methods: A cross-sectional descriptive study on the two hundred mothers caring for children with COVID-19 treated at home in Phu Quoc City, Kien Giang province. Results: The percentage of mothers with good knowledge and attitudes about caring for children withCOVID-19 was 84% and 78.5%, respectively. There was a difference in incorrect knowledge and poor attitudes on COVID-19 prevention and control with ethnicity (p=0,036), household economy (p=0,042, p=0,005, respectively), education level (p=0,001), and occupation (p=0,025).Conclusion: The percentage of mothers with good attitudes in terms of care for COVID-19 in children was not high. The local health system needs to be interested in the relevant factors that provide interventions for the target mothers to improve their attitudes and knowledge in the future.
Keywords: Knowledge, attitudes, mothers, children with COVID-19, treatment at home.